ANALYSIS OF STUDENTS’ ANALYTICAL THINKING SKILL IN ELECTROMAGNETIC INDUCTION CONCEPT USING MINI TESLA COIL - Rengganis, Amalia Puspita; Yulianto, Agus (Physics Communication, 2018)
This study discusses about the effect of using Mini Tesla Coil on students' analytical thinking skill in solving physics problems. This research aims to improve students? analytical thinking skill and to classify students' analytical thinking skill level. The research used mix method with One Group pretest-posttest design. The respondents were 99 students consist of 34 students of 2nd semester, 34 students of 4th semester, and 31 students of 6th semester taken by purposive sampling technique. Demonstration and experiment with Mini Tesla coil were applied on this learning. Collecting data was done through tests and interviews. The significance difference of mean value of analytical thinking skill among student level is determined by ANAVA One Way test, while to know the improvement of analytical thinking skill using the normalized gain (N-Gain) test, and for clarification and deepening data of analytical thinking skill by interview. Based on ANAVA One Way test, Fcount = 5.61 > Ftable = 3.09. These results indicate that there are significant differences on analytical thinking skills among students. Based on the N-Gain test, value of N-Gain is 0.42 - 0.45 which indicates an enhancement on students' analytical thinking skills in the medium category. The result of interview classify the 2nd semester students tend to pre-analytical level, while students of 4th semester and 6th semester tend to partial analytical level. Thus the use of Mini Tesla Coil in the learning is effective to improve analytical thinking skills at all levels of students. Low-level students tend at the pre-analytical thinking whereas the higher level students tend at the partial analytical thinking